Manajemen Sumber Daya Manusia Perspektif Pelatihan dan Pengembangan Tenaga Kerja - Ristanto Edi Saputro (AL-Muqayyad, 2021)
The world's business competition is getting bigger in the era of information and digitalization. Every company needs to develop its products all the time. Even the product must be predictable in the future. In addition, the use of tools and machines must also standardize so that the quality and quantity of products can meet market standards. A company must have human resources or workers who have good skills and knowledge. Problems arise if the workforce owned by the company does not meet the two aspects above. Therefore, companies need to conduct training and development to develop the skills and knowledge of the workforce. There are many benefits for companies that undertake workforce training and development.